Design of polymers for siRNA delivery: Recent progress and challenges. Issue 3 (9th February 2021) - Wang, Hui; Zhang, Song; Lv, Jia; Cheng, Yiyun
Abstract: RNA interference with the ability to specifically silence target genes has shown great potential to treat various diseases. The primary challenge for RNA interference is to effectively and selectively deliver genetic materials such as small interfering RNA (siRNA) to targeted tissues and cells in vivo . Numerous efforts have been made to overcome the extracellular and intracellular barriers during siRNA delivery. In this review, we focused on most recent advances in the design of functional polymers to achieve efficient siRNA delivery via addressing the various parameters, including siRNA binding, serum stability, specific targeting, tissue penetration, cellular internalization, endosomal escape, and intracellular siRNA release. The beneficial roles of assembled polymer nanostructures and polymer‐based hybrid nanocomposites in siRNA delivery were also reviewed. Finally, the challenges and perspectives in the future development of polymer‐based siRNA delivery systems will be discussed. Abstract : RNAi‐mediated gene therapy possesses high specificity, efficiency, and simplicity, which makes siRNA quickly the most popular gene regulation tool. Cationic polymers could be conveniently designed to address the multiple barriers during siRNA delivery including siRNA binding, serum stability, cell selectivity, cellular uptake, endosome escape, and intracellular siRNA release, and hence have shown great potential in siRNA delivery.